Indigenous women participation behavior under one house one farm project of Mymensingh in Bangladesh (Progressive Agriculture, 2017)
The study was conducted to assess the participation behavior of indigenous women by the adoption of one house one farm project in Mymensingh district. The respondents were divided into two groups i.e., project farmers and non-project farmers. The study revealed that the impact of the project was very much satisfactory in terms of education, occupation, farm holding, etc. The participation index was used as a measure of womens participation level in the one house one farm which indicated that 88.0% of the project women obtained a score of 60.0. The results also revealed that the age of the head of households, numbers of trainings imparted to each household, operational holding, frequency of the visit of BRDB personnel, effectiveness of local institutions and off-farm income had significant influence on the participation behavior of the indigenous women. Although, indigenous farmers reported some strengths and opportunities which helped them to cope with the unwanted situation, government and the concerned authorities should come forward to overcome the weaknesses and threats as well.Progressive Agriculture 28 (2): 130-138, 2017